Development of software for steady state drain spacing calculation - BASITH K; Farsana T; Dr. K. V Levan (Guide) (Tavanur 2013 Department of Irrigation and Drainage Engineering)
Development of software for steady state drain spacing calculation
Development of software for steady state drain spacing calculation